2021
DOI: 10.1039/d0sm01162b
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized oscillations, traveling waves, and jammed clusters induced by steric interactions in active filament arrays

Abstract: Autonomous active, elastic filaments that interact with each other to achieve cooperation and synchrony underlie many critical functions in biology. The mechanisms underlying this collective response and the essential ingredients...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…When the vinegar eels are engaged in metachronal waves, the organisms are often touching each other. Chelakkot et al [21] simulated steric interactions between active and elastic filaments in arrays and found that short-ranged steric inter-filament interactions can account for formation of collective patterns such as metachronal waves. Because undulation frequency of C. elegans is slower when under mechanical load imposed by the environment, we assume that steric interactions in our vinegar eels reduce the phase velocity of oscillation.…”
Section: Oscillator Models For Traveling Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…When the vinegar eels are engaged in metachronal waves, the organisms are often touching each other. Chelakkot et al [21] simulated steric interactions between active and elastic filaments in arrays and found that short-ranged steric inter-filament interactions can account for formation of collective patterns such as metachronal waves. Because undulation frequency of C. elegans is slower when under mechanical load imposed by the environment, we assume that steric interactions in our vinegar eels reduce the phase velocity of oscillation.…”
Section: Oscillator Models For Traveling Wavesmentioning
confidence: 99%
“…One approach to modeling metachronal wave formation in cilia or flagella is to model them as flexible filaments that os-cillate or beat when alone. Self-organized metachronal waves then arise due to hydrodynamic [8,11,13,14,[17][18][19][20] or steric [21] interactions between neighboring filaments. Even though a filament can bend and flex, its behavior can approximately be described with an angle or phase which specifies the position of its moving tip (e.g., [13,14]).…”
Section: Introductionmentioning
confidence: 99%
“…Such structures have also been studied in simulation in the context of active dipolar particles representing autophoretic colloids [29,30], as well as swimming microorganisms [31] such as magnetotactic bacteria [32]. In related theoretical studies, constrained or bundled chains of self-propelling colloidal particles [33][34][35][36] have also been shown to exhibit collective instabilities. Elasticity mediated interactions are seen to play critical roles, with the competition between mechanical interactions, steric interactions and activity determining the eventual dynam-ical behavior.…”
Section: Introductionmentioning
confidence: 99%
“…While the appearance of MWs across various systems is extremely robust, the microscopic physics and interactions that result in their emergence are not fully understood ( 11 ). Plausible physical mechanisms include mechanical coupling through the anchoring membrane ( 12 ), local steric interactions within dense arrays ( 13 ), and large-scale fluid motion that induces long-range coupling among cilia ( 14 ). Many models coarse grain the internal mechanics and the fluid–structure interactions by approximating cilia as spheres driven on compliant orbits ( 6 , 15 22 ).…”
mentioning
confidence: 99%